MORPHOSYNTACTIC OF STUDENTS’ WRITING THROUGH SOCIOLINGUISTICS APPROACH IN A HIGHER ISLAMIC EDUCATION - Inayatul Mukarromah (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2020)
Abstract The purpose of this research is to examine of writing, morphology, syntax and also sociolinguistics, especially to the micro and macro linguistics competences to their writing. This method used the combination method of design based research. It is used the theory of Hodley and Reeves The finding result is that 75 % until 85 % students needed material design. More than 60 % students still get mistakes to their writing included inflection and most of them are still less of their knowledge and experience related to the sociolinguistics aspects. The conclusion is that material design is a good solution to assist and overcome students’ writing ability. Keywords : Morphosyntactic, sociolinguistics, inflection, Writing, Material Design